Distribusi Defisiensi Glucose-6-Phosphate Dehydrogenase (G-6-PD) pada Berbagai Populasi Masyarakat di Indonesia - Fransiska Lanni (Universitas Atma Jaya Yogyakarta, 2004)
Glucose-6-phosphate dehydrogenase (G-6-PD) deficiency is the most common human enzymopathy, nearly 400 different biochemical variants of the enzyme have been described worldwide. The heterogeneity of these abnormal hemoglobins are very extensive in some populations such as the results of malarial natural selection and the use as genetic markers for certain populations. As in others malarious areas in Southesat Asia, the presence of G-6-PD deficiency in most Indonesians might be prevalent. Nevertheless the frequencies and epidemiological distribution of these hereditary blood diseases among Indonesians has not been well known yet. This study have screened 2 059 unrelated, apparently healthy adult blood samples from 17 different populations. The present investigation had shown that the G-6-PD deficiency was commonly found in lesser Sunda populations sampled, hold beyond Bali to the east in significant frequencies range from 5% to 13.5%.